2021
DOI: 10.3390/rs14010010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distributions of Ionospheric Irregularities Derived from Regional and Global ROTI Maps

Abstract: Major advancements in the monitoring of both the occurrence and impacts of space weather can be made by evaluating the occurrence and distribution of ionospheric disturbances. Previous studies have shown that the fluctuations in total electron content (TEC) values estimated from Global Navigation Satellite System (GNSS) observations clearly exhibit the intensity levels of ionospheric irregularities, which vary continuously in both time and space. The duration and intensity of perturbations depend on the geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The analysis of the correlations between ROTI and S4/σ Φ using GPS data in low latitude Hong Kong, demonstrates the consistent relationships among the indices for the geomagnetically disturbed days, emphasizing the feasibility of ROTI observations to characterize the ionospheric scintillations [39]. Moreover, the advantage of ROTI over the standard S4 is that it is calculated based on recordings from the regular dual-frequency GNSS receivers, which are relatively more abundant than the specialized scintillation monitoring (S4 and σ Φ ) GNSS receivers across any region [92]. Moreover, in the African longitude sector, Okoh et al [20] showed that there was ~67% agreement in the occurrence of plasma bubbles (detected by an airglow imager) and significant ROTI fluctuations (captured by GNSS receivers within the field of view of the airglow imager).…”
Section: Resultsmentioning
confidence: 67%
“…The analysis of the correlations between ROTI and S4/σ Φ using GPS data in low latitude Hong Kong, demonstrates the consistent relationships among the indices for the geomagnetically disturbed days, emphasizing the feasibility of ROTI observations to characterize the ionospheric scintillations [39]. Moreover, the advantage of ROTI over the standard S4 is that it is calculated based on recordings from the regular dual-frequency GNSS receivers, which are relatively more abundant than the specialized scintillation monitoring (S4 and σ Φ ) GNSS receivers across any region [92]. Moreover, in the African longitude sector, Okoh et al [20] showed that there was ~67% agreement in the occurrence of plasma bubbles (detected by an airglow imager) and significant ROTI fluctuations (captured by GNSS receivers within the field of view of the airglow imager).…”
Section: Resultsmentioning
confidence: 67%
“…Although many researchers have used GPS-based ROTI as a monitoring index for ionospheric irregularities over the equatorial and the polar ionosphere [6,41,42], over the mid-latitude ionosphere it has been less exploited. Several global-based ROTI mapping studies discussed ROTI features over the mid-latitudes [39,43]. Liu et al (2020) [44] demonstrated the statistics of the interhemispheric (E-F layer) coupling of ionospheric irregularities in terms of ROTI over mid-latitude ionosphere by using COSMIC radio occultation data and reported a maximum (~70%) occurrence of E and F region irregularities during June in the Northern Hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…These scintillations monitors, as they provide the carrier pseudorange and phase besides the signal intensity, the TEC and the parameters rate of TEC (ROT) and ROT index (ROTI) (Pi et al 1997) can also be determined. Jesus et al (2020) and Nguyen et al (2022), among other authors, pointed out that ROTI and S 4 are well correlated. The main aim of this work is to provide the description of the GNSS-based scintillation monitoring networks at the Brazilian territory.…”
Section: Introductionmentioning
confidence: 88%